Use of Visual Analysis to Investigate Networked Learning in Online Forums - Ferguson, Rebecca (Proceedings of the International Conference on Networked Learning, 2012)
Asynchronous online forums such as FirstClass are frequently used in many educational settings to link networks of learners. They offer opportunities for knowledge-building dialogue and for the exchange of learning resources, but many students struggle to make effective use of them. Researchers have therefore been concerned to investigate how learners successfully build knowledge together in online forums and which skills and literacies are likely to help users to learn in these environments. To date, much of this research has focused on the textual elements of online forum dialogue. This paper acknowledges the importance of studying these textual elements, but presents visual analysis as a complementary tool that can significantly extend understanding of activity in these forums. Asynchronous dialogue, like written text, is typically both verbal and visual, with much of its meaning carried by a range of visual features, including layout and typographical elements. These aspects of forum data require analysis of the composition of the dialogue alongside its content. In the case of such composite texts, with meanings realised through different semiotic codes, visual and verbal elements interact and should be analysed as an integrated whole. This semiotic approach draws attention to the syntax of images as a source of meaning and to the structuring principles that enable viewers to make sense of the layout of text and images. These principles include salience, frames, vectors and reading paths. This paper demonstrates ways in which analysis that makes use of these structuring principles can increase understanding of online exchanges between learners. It takes as an exemplar a series of forum postings that were shared in the formal setting of an online course at the UK’s Open University. It shows that the construction of knowledge in an online forum is heavily reliant on visual elements of the online interaction, and that a focus on words alone does not make it clear either how this construction takes place or why it fails to take place on some occasions. Visual analysis shows that groups of learners use affordances of forum software to increase the salience of some elements of the dialogue and to increase the coherence of their discussion.